An Unexpected Complete Remission of Advanced Intestinal-Type Vulvar Adenocarcinoma after Neoadjuvant Chemotherapy: A Case Report and a Literature Review. (6th November 2013) - Musella, Angela; Marchetti, Claudia; Salerno, Laura; Vertechy, Laura; Iadarola, Roberta; Pecorella, Irene; Panici, Pierluigi Benedetti
Abstract : Vulvar cancer represents approximately 3%–5% of all gynecological malignancies. Squamous cell carcinoma is the most frequent histotype, whereas melanomas, adenocarcinomas, basal cell carcinomas, and sarcomas are much less common. Intestinal-type adenocarcinoma is a rare variant of vulvar carcinoma with only few cases found in the literature. The origin of this neoplasia is still much debated, but the most reliable hypothesis is the origin from cloacal remnants that may persist in the adult in different organs. Because of its extremely low incidence, the optimal management of this kind of vulvar cancer is still debated. We report the case of a woman affected by advanced intestinal-type vulvar adenocarcinoma, who achieved a complete clinical and pathological response after neoadjuvant chemotherapeutic treatment with platinum and paclitaxel.